Europäischer Structur- und Investitionsfonds 2014-2020. Gewerkschaftshanbuch - Denagtergal, Claude; Fitzgerald, Ruairi (Brüssel, 2015)
"The aim of this handbook is to provide a comprehensive resource for trade unionists with regards to two aspects: 1.Their role in the management and use of European structural and investment funds (ESI Funds) 2.The use of ESI funds to support trade union activity"